Altered phenotypic and functional characteristics of CD3(+)CD56(+) NKT-like cells in human gastric cancer - Peng, Liu-sheng (Oncotarget, 2016)
CD3(+)CD56(+) natural killer T (NKT)-like cells are a group of CD3(+) T cells sharing characteristics of NK and T cells and constitute a major component of host anti-tumor immune response in human cancer. However, the nature, function and clinical relevance of CD3(+)CD56(+) NKT-like cells in human gastric cancer (GC) remain unclear. In this study, we showed that the frequencies of CD3(+)CD56(+)NKT-like cells in GC tumors were significantly decreased and low levels of tumor-infiltrating CD3(+)CD56(+) NKT-like cells were positively correlated with poor survival and disease progression. Most CD3(+)CD56(+)NKT-like cells in GC tumors were CD45RA(−)CD27(+/−) central/effector-memory cells with decreased activity and lower expression levels of CD69, NKG2D and DNAM-1 than those in non-tumor tissues. We further observed that tumor-infiltrating CD3(+)CD56(+) NKT-like cells had impaired effector function as shown by decreased IFN-γ, TNF-α, granzyme B and Ki-67 expression. Moreover, in vitro studies showed that soluble factors released from GC tumors could induce the functional impairment of CD3(+)CD56(+) NKT-like cells. Collectively, our data indicate that decreased tumor-infiltrating CD3(+)CD56(+) NKT-like cells with impaired effector function are associated with tumor progression and poor survival of GC patients, which may contribute to immune escape of GC.